Few-shot Learning for Joint Classification of Instrument, Pitch, and Playing Technique of Tones Produced by Bowed String Instruments - Jacobs, J. Pieter (University of Pretoria, 2024)
Dissertation (MEng(Computer Engineering))--University of Pretoria, 2023.